Patch effect on the bending behavior of double-cracked hat-shaped carbon fiber composite beams - Albayrak, Mustafa; Ballıkaya, Hasan; Kaman, Mete Onur (Walter de Gruyter Gmbh, 2026)
In this study, reinforced composite panels with hat profiles were produced from woven carbon fiber fabrics by vacuum infusion methods. Double cracks of different sizes were opened on the crown surface of these panels in perpendicular axes. The cracked specimens were then repaired with wet patches under vacuum. Three-point bending tests were performed on the uncracked, cracked and patched specimens to examine their mechanical behavior. In the numerical part, the Puck damage criterion was used for damage initiation and the material property degradation method was used for damage progression. As a result of the experiments and analyses, it was observed that the absorbed energy of the structure decreased by 10 % with the opening of a 40 & times; 20 mm long crack on the reinforced panel. However, it was determined that 200 % more absorbed energy was obtained com-pared to the uncracked specimen after the repair with the patch. In the patched specimens, fiber crushing was determined as the dominant damage type on the patch surface where the semi-spherical moving cylinder touched under bending load. However, fiber breaks were observed along the length of the specimen at the junction edge of the crown and web surfaces.
Keywords: CFRP; double crack; patch; mpdg; progressive failure analysis